Beyond the Competencies Agenda in Large-Scale International Assessments: A Confucian Alternative - Tan, Charlene (Philosophical Inquiry in Education, 2019)
This article examines a Confucian conception of competence and its corresponding response to the competencies agenda that underpins international large-scale assessments such as the Programme for International Student Assessment (PISA). It is argued that standardised transnational assessments is underpinned by technical rationality that emphasises proficiency in discrete skills for their instrumental worth at the expense of moral cultivation and personal mastery. Challenging the competencies agenda, this paper draws upon a relational model of competence proposed by Jones and Moore (1995) that views competence as essentially communal, situated within social practices, and manifested through tacit achievement. A Confucian notion of competence is advocated where skills are premised on the virtue of ren (humanity) and demonstrated through appropriate judgement in everyday settings. A Confucian perspective offers an alternative to the behaviourist and generic notions of performance in global assessments by highlighting the social, cultural and ethical dimensions of competence.